Onset features and time to diagnosis in Friedreich’s Ataxia - Indelicato, Elisabetta; Nachbauer, Wolfgang; Eigentler, Andreas; Amprosi, Matthias; Matteucci Gothe, Raffaella; Giunti, Paola; Mariotti, Caterina; Arpa, Javier; Durr, Alexandra; Klopstock, Thomas; Schöls, Ludger; Giordano, Ilaria; et al. (Orphanet journal of rare diseases, 2020)
Background In rare disorders diagnosis may be delayed due to limited awareness and unspecific presenting symptoms. Herein, we address the issue of diagnostic delay in Friedreich’s Ataxia (FRDA), a genetic disorder usually caused by homozygous GAA-repeat expansions. Methods Six hundred eleven genetically confirmed FRDA patients were recruited within a multicentric natural history study conducted by the EFACTS (European FRDA Consortium for Translational Studies, ClinicalTrials.gov -Identifier NCT02069509). Age at first symptoms as well as age at first suspicion of FRDA by a physician were collected retrospectively at the baseline visit. Results In 554 of cases (90.7%), disease presented with gait or coordination disturbances. In the others ( n = 57, 9.3%), non-neurological features such as scoliosis or cardiomyopathy predated ataxia. Before the discovery of the causal mutation in 1996, median time to diagnosis was 4(IQR = 2–9) years and it improved significantly after the introduction of genetic testing (2(IQR = 1–5) years, p < 0.001). Still, after 1996, time to diagnosis was longer in patients with a) non-neurological presentation (mean 6.7, 95%CI [5.5,7.9] vs 4.5, [4.2,5] years in those with neurological presentation, p = 0.001) as well as in b) patients with late-onset (3(IQR = 1–7) vs 2(IQR = 1–5) years compared to typical onset < 25 years of age, p = 0.03). Age at onset significantly correlated with the length of the shorter GAA repeat (GAA1) in case of neurological onset (r = − 0,6; p < 0,0001), but not in patients with non-neurological presentation (r = − 0,1; p = 0,4). Across 54 siblings’ pairs, differences in age at onset did not correlate with differences in GAA-repeat length (r = − 0,14, p = 0,3). Conclusions In the genetic era, presentation with non-neurological features or in the adulthood still leads to a significant diagnostic delay in FRDA. Well-known correlations between GAA1 repeat length and disease milestones are not valid in case of atypical presentations or positive family history.